Exploring the Emotional Experience During Instant Messaging Among Young Adults: An Experimental Study Incorporating Physiological Correlates of Arousal - Camerini, Anne-Linda; Marciano, Laura; Annoni, Anna Maria; Ort, Alexander; Petrocchi, Serena (Frontiers in Psychology, 2022)
Instant messaging (IM) is a highly diffused form of communication among younger populations, yet little is known about the emotional experience during IM. The present study aimed to investigate the emotional experience during IM by drawing on the Circumplex Model of Affect and measuring heart rate and electrodermal activity as indicators of arousal in addition to self-reported perceived emotional valence. Using an experimental design, we manipulated message latency (i.e., response after 1 minute versus 7 minutes) and message valence (positive versus negative response). Based on data collected from 65 young adults (50% male; Mage = 23.28, SD = 3.75), we observed arousal as participants’ electrodermal activity levels increased from the time a fictitious peer started typing a response to the receipt of that response, especially in the delayed condition. Electrodermal activity levels also increased in both the positive and the negative message conditions. No changes were observed for heart rate. Participants’ self-report perceived emotional valence revealed that positive messages were evaluated as more pleasant, while no difference in the self-report was found for message latency. These findings shed light on the emotional experience during IM by adding valuable insights on the physiological processes underlying the anticipation of social reward, especially during delayed instant message exchange as a form of Human-Computer-Interaction.